Pendampingan Pendidik dan Tenaga Kependidikan untuk Mewujudkan Zona Berkarakter Mulia - Susanto (Bulletin of Community Engagement, 2025)
The community service program was designed to enhance the quality of a character-based educational ecosystem at the Elementary School of Character Genius Islamic School. The program utilized the Asset-Based Community Development (ABCD) approach, a framework for community development that leverages existing local potentials and assets. The school was identified to possess various strengths that could be further developed to establish a Noble Character Zone. Implemented from January to August 2024, the program engaged 60 educators and staff members from Genius Islamic School. The research employed multiple data collection methods, including observations, interviews, and document analysis. Data analysis was carried out using the Miles and Huberman technique. The program was executed in five key stages: (1) identifying and mobilizing assets, (2) communicating, (3) designing, (4) implementing, and (5) evaluating. Findings from the initiative revealed that a policy framework supporting character development was already in place, achieving an implementation rate of 87%. Educator and staff engagement reached 82%, the implementation mechanism scored 84%, and infrastructure development achieved 81%. Student involvement stood at 85%, while parental participation matched the policy framework rate at 87%.This community service initiative significantly contributed to enhancing character education outcomes within the institution. It also raised awareness of the importance of leveraging school-based character development initiatives tailored to each institution's unique strengths. Furthermore, it provides a valuable model for other schools seeking to implement character-strengthening innovations through policy and practice, guided by the vision of realizing a Noble Character Zone.